ANALISIS HUBUNGAN INFORMASI COSTVOLUMEPROFIT (CVP) DAN INFORMASI REALISASI ANGGARAN TAHUN LALU UNTUK PENILAIAN EFEKTIFITAS PERENCANAAN USAHA (STUDI KASUS KOPERASI SIMPAN PINJAM DI KOTAMADIASEMARANG) - Luhgiatno .; Widaryanti .; Ndaruningpuri W. (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2007)
This study has objective, first, to investigate how koperasi simpan pinjam in Kotamadia Semarang make its business planning with CostVolumeProfit(CVP) information and realization on budget last year information. Second, to observe the effect of CVP and realization of budget last year information with business planning efectivity in koperasi simpan pinjam KotamadiaSemarang. Sample in this study are 13 kospin that have been listed in Dinas Koperasi Usaha Kecil Menengah Kota Semarang until April 2007. The statistical method used in this study is multiple linier regresion. Quesioner is used to data collecting.The deskriptif result show that kospin Kotamadia Semarang, in majority have enough category in business planning, CVP and realization of budget last year information. Statistical result show that CVP information have significant effect to business planning efectivity. Realization of budget last year information have positif significant effect to business planning efectivity. With simultan test, CVP and realization of budget last year information effect to business planning efectivity.